What Should I do and Who’s to blame? A cross-national study on youth’s attitudes and beliefs in times of COVID-19 - De Moor Elisabeth L.; Cheng Ting-Yu; Spitzer Jenna E.; Berger Christian; Carrizales Alexia; Garandeau Claire F.; Gerbino Maria; Hawk Skyler T.; Kaniušonytė Goda; Kumru Asiye; Malonda Elisabeth; Rovella Anna; et al. (Public Library of Science, 2025)
The COVID-19 crisis has had a major impact on youth. This study examined factors associated with youth’s attitudes towards their government’s response to the pandemic and their blaming of individuals from certain risk groups, ethnic backgrounds, and countries or regions. In a sample of 5,682 young adults (Mage = 22) from 14 countries, lower perceived burden due to COVID-19, more collectivistic and less individualistic values, and more empathy were associated with more positive attitudes towards the government and less blaming of individuals of certain groups. Youth’s social identification with others in the pandemic mediated these associations in the same direction, apart from the COVID-19 burden on attitudes, which had a positive indirect effect. No evidence of country-level moderation was found.